The relationship between small intestinal bacterial overgrowth and constipation in children – a comprehensive review - Mares, Cristina Roxana; Săsăran, Maria Oana; Mărginean, Cristina Oana (Frontiers in Cellular and Infection Microbiology, 2024)
Small intestinal bacterial overgrowth (SIBO) is characterized by an increase in the bacterial population of the small intestine due to an imbalance between the amount of bacteria and the intestinal barrier. Pediatric SIBO presents with a wide spectrum of symptoms, ranging from mild gastrointestinal complaints to malabsorption or malnutrition. Breath tests are commonly used as noninvasive diagnostic tools for SIBO, but a standardized methodology is currently unavailable. Intestinal flora produces methane which slows intestinal transit and increases the contractile activity of small intestine. Emerging literature suggests a correlation between overgrowth of methanogenic bacteria in the intestines and constipation. Treatment of SIBO involves administration of antibacterial therapy in addition to management of underlying conditions and optimal dietary adjustments. However, research on antibiotic treatment for pediatric patients with constipation and SIBO is limited and has yielded conflicting results. In the current review, we summarize the stateof-the-art of the field and discuss previous treatment attempts and currently used regimens for SIBO patients with constipation, with a focus on pediatric populations. with symptoms of constipation-predominant syndrome in 54.6% of children and diarrheapredominant type in the rest of children, according to Hutyra et al (Hutyra and Iwańczak, 2010).The most common symptoms of SIBO are abdominal pain, diarrhea, constipation, flatulence, belching, foul-smelling stools with mucus, nausea and stunted growth (Cho et al., 2023). SIBO occurs when the balance between bacteria and the intestinal tract protection barrier is altered (Banaszak et al., 2023). Typically, the bacterial count in the proximal bowel is around 10 2 CFU)/mL, which increases gradually towards the terminal ileum (Rana and Bhardwaj, 2008). The mechanisms that control bacterial proliferation are gastric acid secretion, digestive tract integrity, propulsive peristalsis and IgA immunoglobulins (Hammer et al., 2022). Therefore, numerous conditions in which these mechanisms are altered are associated with SIBO: ileo-cecal valve resection; small bowel diverticulosis; treatment with proton pump inhibitors, atrophic gastritis or gastric bypass which lower gastric pH; treatment with drugs that slow intestinal motility (antidiarrheals, anticholinergics) or abnormal small intestinal motility in different pathologies (celiac disease, inflammatory bowel disease, scleroderma, diabetes, Parkinson's disease)(